(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the relationship between arm muscle strength and arm length on the accuracy of the upper serve in extracurricular volleyball students at SMK Negeri 4 Palembang. The research method used is correlational. The research sample was 36 students (20 boys and 16 girls) selected using the total sampling technique. The instruments used included an arm muscle strength test through push-ups, arm length measurements using a measuring tape, and an upper serve accuracy test. The results showed that there was a perfect relationship between arm muscle strength and the accuracy of the upper serve, with a correlation value of R = 0.946 in male students and R = 0.933 in female students. Arm length also had a moderate relationship to the accuracy of the upper serve, with a correlation value of R = 0.613 in male students and R = 0.589 in female students. Regression analysis showed that arm muscle strength and arm length together contributed perfectly to the accuracy of the upper serve, with a value of R = 0.946 in male students and R = 0.940 in female students. These results indicate that arm muscle strength and arm length are important factors in improving the accuracy of the upper serve. These findings provide implications for coaches to develop physical training programs that focus more on strengthening students’ arm muscles and overhead serve techniques.